LINGUISTIC SPECIFICATION OF MERONYMY IN ENGLISH AND UZBEK LANGUAGES (Ustozlar uchun, 2026)
The present research is devoted to the comparative linguistic analysis of meronymy in English and Uzbek languages. Meronymy, which expresses the semantic relation between a whole and its constituent parts, occupies a significant place in lexical semantics, cognitive linguistics, and structural linguistics. The study investigates the structural, semantic, functional, and cognitive peculiarities of meronymic relations in two genetically unrelated languages belonging to different language families. English, as an Indo-European language, and Uzbek, as a Turkic language, demonstrate both universal and language-specific features in the realization of part-whole relationships. The thesis explores the theoretical foundations of meronymy and examines its place among lexical-semantic relations such as synonymy, antonymy, hyponymy, and polysemy. Special attention is paid to the classification of meronymic relations, including component-object, member-collection, portion-mass, phase-process, and place-area relations. The study further analyzes how meronymic units function in literary texts, everyday discourse, phraseological expressions, and terminological systems in both languages.